Geometría, esquemas e idealización: una módica defensa de la filosofía de la geometría de Kant - Peláez Cedrés, Álvaro J. (Revista de Filosofía, 2008)
In this work, I shall defend the importance of transcendental schemata for understanding the kind of things that Kant had in mind when he talked about geometric objects or representations. I will argue for the idea that in general, the transcendental schemata are a set of rules that allow the transformation of one figure into another, and also the representation of the properties that remain invariant under those rules, which are the genuine objects of cognition in a judgment. Likewise, I will show not only the relations that, in my opinion, the Kantian philosophy has with the geometry of his time, but also how such a philosophy can be used for understanding the late development of that discipline.